Towards a pan-European typology of sheep and goat farms: A meta-analysis - Theodoridis A.; Ragkos A.; Zaralis K.; Smith L.; Arsenos G. (Innovation for sustainability in sheep and goats, 2019)
The objective of this work was to develop a single pan-European typology of sheep and goat farming systems. Initially a thorough review of all the available literature was undertaken and a total of 45 typological studies were identified. A meta-analysis of these typologies led to the formation of a “broad typology” that specified 13 types of sheep farms and 5 types of goat farms. This typology included types described by their prevailing characteristics such as the level of grazing and intensification, production aims, their environmental impact and awareness and the level of technology uptake at farm level. These types were not discrete and mutually exclusive to all countries, so in a second step they were refined using inputs and knowledge of industry representatives of the sheep/goat sectors across several European countries and Turkey. This process led to the production of the final typology that consisted of five types for sheep farms and five four types for goat farms. Farms of cross-cutting characteristics such as organic, PDO, PGI, pluriactivity etc. were included under these farm types when appropriate.
2. Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2017/10/03-05, Vitoria-Gasteiz (Spain)